The Industrialized Designer: Gender, Identity and Professionalization in Britain and the United States, 1930-1980 - Armstrong, Leah (Manchester University Press, 2024)
What does it mean to be called an industrial designer? This book traces the remarkable rise of this professional identity in historical perspective from a position of anonymity in the early twentieth century, to mid-century professionalisation, to decline and disintegration by 1980. Was bedeutet es, als Industriedesigner bezeichnet zu werden? Dieses Buch zeichnet den bemerkenswerten Aufstieg dieser beruflichen Identität in historischer Perspektive nach, von einer Position der Anonymität zu Beginn des zwanzigsten Jahrhunderts über die Professionalisierung in der Mitte des Jahrhunderts bis hin zum Niedergang und der Auflösung um 1980.